Bacteriological investigation of udder lobes of cows with mastitis slaughtered in the Elazig region - Gülcü, HB; Ertas, HB (Scientific Technical Research Council Turkey, 2004)
Bacteriological examinations were performed on 206 mammary tissue samples taken from 160 cows with mastitis in Elazig. The isolates were identified as Staphylococcus aureus (39.04%). Staphylococcus epidermidis (17.81%), Actinomyces pyogenes (14.38%), Escherichia coli (8.9%), Streptococcus agalactiae (6.16%), Streptococcus uberis (4.11%), Streptococcus dysgalactiae (3.42%), Corynebacterium bovis (1.37%), Pasteurella haemolytica (1.37%) and Bacillus cereus (1.37%).
Keywords: cow; mastitis; bacteria; udder lobes